Successful medical management of tuberculous broncho-oesophageal fistula - Madan, Karan (BMJ Publishing Group, 2014)
Broncho-oesophageal fistula (BEF) of benign aetiology is rare. BEF is a rare complication of intrathoracic involvement with tuberculosis. A high index of suspicion and appropriate investigations can lead to achieving an early diagnosis following which appropriate management can be timely instituted. Surgery can be avoided if the condition is recognised in early stages. We present a case of a young female patient with tubercular mediastinal lymphadenopathy complicated by left broncho-oesophageal fistulisation. Timely initiation of conservative medical management was followed by an uneventful recovery.